2018
DOI: 10.1002/cne.24486
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the corpus callosum in wild and domestic canids: Insights into the domesticated brain

Abstract: All domesticated mammals exhibit marked reductions in overall brain size, however, it is unknown whether the corpus callosum (CC), an integral white matter fiber pathway for interhemispheric cortical communication, is affected by domestication differentially or strictly in coordination with changes in brain size. To answer this question, we used quantitative magnetic resonance imaging to compare the midsagittal cross-sectional areas of the CC in 35 carnivore species, including eight wild canids and 13 domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…In addition, we also calculated the cross‐sectional area of the corpus callosum and the cortical gyrification index for each specimen using the approaches detailed in previous studies (see Manger, Hemingway, Haagensen, & Gilisssen, 2010; Manger, Prowse, Haagensen, & Hemingway, 2012; Pillay & Manger, 2007; Spocter et al, 2018; Zilles, Armstrong, Moser, Schleicher, & Stephan, 1989). In Figure 2 we present an outline of the ROI methodology with sample MR images through the brain of the African wild dog.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also calculated the cross‐sectional area of the corpus callosum and the cortical gyrification index for each specimen using the approaches detailed in previous studies (see Manger, Hemingway, Haagensen, & Gilisssen, 2010; Manger, Prowse, Haagensen, & Hemingway, 2012; Pillay & Manger, 2007; Spocter et al, 2018; Zilles, Armstrong, Moser, Schleicher, & Stephan, 1989). In Figure 2 we present an outline of the ROI methodology with sample MR images through the brain of the African wild dog.…”
Section: Methodsmentioning
confidence: 99%
“…Using Phylogenetic Generalized Least Squares (PGLS) regression analysis we quantitatively compared the average values for the African wild dog with allometric data obtained from a subset of other mammals used in previous studies by our group (Grewal et al, 2020;Manger et al, 2010Manger et al, , 2012Maseko et al, 2011Maseko et al, , 2012Patzke et al, 2015;Pillay & Manger, 2007;Spocter, Uddin, et al, 2018). Our goal here was not to re-evaluate the published data but rather to show through superimposition where the average values for the African wild dog are found in relation to other mammals.…”
Section: Volumetric Data and Descriptive Statisticsmentioning
confidence: 99%
“…Although limited in scope, recent allometric analyses have suggested that domestic dogs (i.e., golden retriever) might possess a larger number of cortical neurons when compared with other larger‐brained carnivores (Jardim‐Messeder et al, 2017). Spocter et al (2018) recently reported increased variability in canine corpus callosum morphology and demonstrated that amidst the general pattern of conservation in corpus callosum proportions among the canids, there still remained evidence of breed‐specific patterning in dogs, likely influenced by artificial selection. More recently, Hecht et al (2019) provided additional evidence for the influence of artificial selection on canine brains through observations of breed‐specific specializations in brain networks.…”
Section: Introductionmentioning
confidence: 99%
“…These latter measurements revealed links with individual variation in behavior, including in brain regions that did not show volumetric differences, notably, the hypothalamus. Additionally, Network 3 consisted primarily of the hypothalamus and prefrontal cortex, two regions strongly implicated in both fox and dog domestication [8][9][10][19][20][21][30][31][32][33] . In this network, factor loadings did not differentiate the tame from aggressive strains; rather, the selectively-bred strains together were differentiated from the conventional strain ( Figure 3C).…”
Section: Discussionmentioning
confidence: 99%